Penerapan Manajemen Risiko Berbasis ISO 31000 pada Industri Percetakan Digital: Studi Kasus Panda Project - Naura Rahadhatul Aisy; Aulia Silvana; Tariza Mega Pratiwi Garini; Haura Nurul Ilmi; Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
The digital printing industry is facing increasingly competitive dynamics due to the emergence of many new service providers, changing customer preferences, fluctuating raw material prices, and potential machine operational disruptions. This study aims to analyze the implementation of ISO 31000-based risk management in the Panda Project printing business using a qualitative descriptive method with a case study approach through the four main stages of ISO 31000: risk identification, risk analysis, risk evaluation, and risk mitigation. Data collection was conducted through in-depth interviews with the Panda Project printing business owner and direct observation of business processes. Panda Project is categorized as an MSME (Micro, Small, and Medium Enterprise), a productive business managed independently with limited capital and workforce, but making a significant contribution to the economy and workforce absorption in Indonesia. The research results show that Panda Project experiences various dominant risks, including unstable customer demand, late payments, increases in raw material prices, production machine disruptions, and decreased digital marketing effectiveness. To minimize these impacts, mitigation strategies implemented include finding alternative suppliers, maintaining financial records, optimizing digital promotions, regular machine maintenance, and implementing production standard operating procedures (SOPs) to reduce operational errors. Overall, the implementation of ISO 31000 helps Panda Project's MSMEs manage risk.